Neuromuscular Diseases and Bone - Iolascon, Giovanni; Paoletta, Marco; Liguori, Sara; Curci, Claudio; Moretti, Antimo (Frontiers in Endocrinology, 2019)
Neuromuscular diseases (NMDs) are inherited or acquired conditions affecting skeletal muscles, motor nerves, or neuromuscular junctions. Most of them are characterized by a progressive damage of muscle fibers with reduced muscle strength, disability, and poor health-related quality of life of affected patients. In this scenario, skeletal health is usually compromised as a consequence of modified bone–muscle cross-talk including biomechanical and bio-humoral issues, resulting in increased risk of bone fragility and fractures. In addition, NMD patients frequently face nutritional issues, including malnutrition due to feeding disorders and swallowing problems that might affect bone health. Moreover, in these patients, low levels of physical activity or immobility are common and might lead to overweight or obesity that can also interfere with bone strength features. Also, vitamin D deficiency could play a critical role both in the pathogenesis and in the clinical scenario of many NMDs, suggesting that its correction could be useful in maintaining or enhancing bone health, especially in the early phases of NMDs. Last but not least, specific disease-modifying drugs, available for some NMDs, are frequently burdened with adverse effects on bone tissue. For example, glucocorticoid therapy, standard of care for many muscular dystrophies, prolongs long-term survival in treated patients; nevertheless, high dose and/or chronic use of these drugs are a common cause of secondary osteoporosis. This review addresses the current state of knowledge about the factors that play a role in determining bone alterations reported in NMDs, how these factors can modify the biological pathways underlying bone health, and which are the available interventions to manage bone involvement in patients affected by NMDs. Considering the complexity of care of these patients, an interdisciplinary and multimodal management strategy based on both pharmacological and non-pharmacological interventions is recommended, particularly targeting musculoskeletal issues that are closely related to functional independence as well as social implications.